Copy number variation of human AMY1 is a minor contributor to variation in salivary amylase expression and activity. Issue 1 (December 2017) - Carpenter, Danielle; Mitchell, Laura; Armour, John
Abstract Background Salivary amylase in humans is encoded by the copy variable geneAMY1 in the amylase gene cluster on chromosome 1. Although the role of salivary amylase is well established, the consequences of the copy number variation (CNV) atAMY1 on salivary amylase protein production are less well understood. The amylase gene cluster is highly structured with a fundamental difference between odd and evenAMY1 copy number haplotypes. In this study, we aimed to explore, in samples from 119 unrelated individuals, not only the effects ofAMY1 CNV on salivary amylase protein expression and amylase enzyme activity but also whether there is any evidence for underlying difference between the common haplotypes containing odd numbers ofAMY1 and even copy number haplotypes. Results AMY1 copy number was significantly correlated with the variation observed in salivary amylase production (11.7% of variance, P < 0.0005) and enzyme activity (13.6% of variance, P < 0.0005) but did not explain the majority of observed variation between individuals.AMY1 -odd andAMY1 -even haplotypes showed a different relationship between copy number and expression levels, but the difference was not statistically significant (P = 0.052). Conclusions Production of salivary amylase is correlated withAMY1 CNV, but the majority of interindividual variation comes from other sources. Long-range haplotype structure may affect expression, but this was not significant in our data.